THE INFLUENCE OF CORPORATE SOCIAL RESPONSIBILITY, FAMILY OWNERSHIP, AND INSTITUTIONAL OWNSHIP ON TAX AVOIDANCE FOR MANUFACTURING COMPANIES - Gianti, Sabrina; Ratnawati, Dyah (Yayasan Education and Social Center, 2024)
The purpose of the study was to examine the influence of Corporate Social Responsibility, Family Ownership, and Institutional Ownership on Tax Avoidance in manufacturing companies from 2019 to 2022. This study employs a form of quantitative research that utilizes secondary data extracted from financial reports and business sustainability reports. The study sample consists of 226 manufacturing companies that were listed on the Indonesian Stock Exchange during the period of 2019-2022. The samples were chosen using the purposive sampling technique, applied to a total of 176 data points collected from 44 company samples throughout a 4-year research period. The data analysis employed double regression analysis techniques to examine the relationship between corporate social responsibility, family ownership, institutional ownership, and tax avoidance. The research findings indicate that these factors have a considerable negative impact on tax avoidance. Therefore, if the corporation implements higher levels of corporate social responsibility, family ownership, and institutional ownership, it will effectively prevent any potential instances of tax avoidance